ARTIKULASI IDEOLOGI POLITIK MASYARAKAT ISLAM DI INDONESIA - Ernas (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2014)
This writing seeing reinforce that has grown recently that in the case of Indonesia, commitment no longer parallel with religious orientation and political expression. Some event as political factors on and election shows that religion is no longer a factor in influencing determinan political choice. Majority muslims in indonesia to regard as different political arena by religiousity. Then factors as political leadership, principal capacity, trackrecord and personal images determinant in the choice of politics. Nevertheless, this studies also indicated that changes and shifting political orientation voters not altogether may be claimed as the success of the process of secularization in political modernization in indonesia. It appears the phenomenon of pragmatism and hypocritizm become indonesia chief symptom in politics today. These symptoms shows that political arena just a sign of the power struggle and efforts to hunt down interest (rente) on the parties involved in it. In practice this kind of political, the interest of the people can no longer be the locus of the main in the ideology and political vision. If a political party or the political power of Islam in Indonesia do not want to have setbacks and landed in the defeat and destruction is available continuously, we must immediately conduct reorientasi and political reposition. Islamic Politic were not political can depend on the belief an absurd sociological that (the majority of people islam in indonesia were muslim , then they will certainly choose of the Islamic Party). On the other hand if we want to become the strength of dominant political , the political power of Islam must be able to ideology reposition, political agenda and the acts of political and more substantive and earthiness contemporary according to the need of the Islamic Community of Indonesia.